High-performance flexible-film supercapacitors of layered hydrous RuO2/poly(3, 4-ethylenedioxythiophene)-poly(styrenesulfonate) through vacuum filtration. (1st September 2018) - Chang, Yanan; Zhou, Weiqiang; Wu, Jing; Ye, Guo; Zhou, Qianjie; Li, Danqin; Zhu, Danhua; Li, Tongxin; Nie, Guangming; Du, Yukou; Xu, Jingkun
Abstract: A micron-thick flexible layered RuO2 ·1.18H2 O/PEDOT-PSS film with high electric conductivity of about 306 S cm −1 (sheet resistance of film of 7.1 Ω sq −1 ) was prepared using commercial PEDOT-PSS dispersion and RuO2 ·1.18H2 O nanoparticles through a simple, low-cost vacuum filtration technology. The layered flexible film could be used as a rope to hang up 300 gram weight and as a conducting wire in a circuit to light a blue LED lamp. The symmetrical supercapacitor based on the layered flexible films showed high specific capacitance of 591 F g −1 (volumetric specific capacitance of 530 F cm −3 ) at 10 mV s −1, excellent long-term cycling stability (capacitance retention of 91.5%) after 5000 cycles, and high energy density of 18 Wh kg −1 at high power density of 5000 W kg −1 . The flexible film as function as current collector and active material simultaneously will have practical application in miniaturized flexible supercapacitors. Graphical abstract: Image 1 Highlights: Flexible layered RuO2 ·1.18H2 O/PEDOT-PSS film was prepared through filtration. The film had good mechanical property and high electrical conductivity. The film showed high specific capacitance of 591 F g -1  at 10 mV s −1 . The film exhibited high energy density of 18 Wh kg −1 at 5000 W kg −1 . The capacitance retention of the film was 91.5% after 5000 cycles at 10 A g −1 .